2003
DOI: 10.1146/annurev.psych.54.101601.145124
|View full text |Cite
|
Sign up to set email alerts
|

Operant Conditioning

Abstract: Operant behavior is behavior "controlled" by its consequences. In practice, operant conditioning is the study of reversible behavior maintained by reinforcement schedules. We review empirical studies and theoretical approaches to two large classes of operant behavior: interval timing and choice. We discuss cognitive versus behavioral approaches to timing, the "gap" experiment and its implications, proportional timing and Weber's law, temporal dynamics and linear waiting, and the problem of simple chain-interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
213
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 336 publications
(231 citation statements)
references
References 124 publications
2
213
1
Order By: Relevance
“…Experiments have shown that the contingency makes surprising little difference to performance (see Catania, Yohalem &Silverman, 1980, andreview in Staddon &Cerutti, 2003). Providing the response contingency for food in the terminal link is maintained, it can be omitted in earlier links with little effect on key pecking, as long as stimulus changes continue to take place as before (i.e., the fixed-interval contingency is replaced with a fixed-time contingency -this is termed a fixedinterval clock, because the successive stimulus changes signal the lapse of postfood time).…”
Section: Conditioned Reinforcementmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments have shown that the contingency makes surprising little difference to performance (see Catania, Yohalem &Silverman, 1980, andreview in Staddon &Cerutti, 2003). Providing the response contingency for food in the terminal link is maintained, it can be omitted in earlier links with little effect on key pecking, as long as stimulus changes continue to take place as before (i.e., the fixed-interval contingency is replaced with a fixed-time contingency -this is termed a fixedinterval clock, because the successive stimulus changes signal the lapse of postfood time).…”
Section: Conditioned Reinforcementmentioning
confidence: 99%
“…There are several papers deriving matching from various maximizing principles, e.g., Rachlin (1978) and Staddon and Motheral (1978), although these have not gone unchallenged (Herrnstein & Heyman 1979;Heyman, 1979;Staddon & Motheral, 1979). Reviews are Williams (1988) and Staddon & Cerutti (2003).…”
mentioning
confidence: 99%
“…In the study reported here, we selected and studied neurobehavioral functions using the so-called schedule-controlled operant behavior (SCOB) procedure. This procedure has been widely used in the fields of behavioral pharmacology and toxicology because it is highly sensitive in detecting a subtle alterations (see reviews in [15][16][17][18]). …”
Section: Introductionmentioning
confidence: 99%
“…When events that function as reinforcers for certain organisms under certain conditions are identified, for example, food for a deprived rat, empirical and practical investigations can be conducted. The study of reinforcement schedules is a good example of empirical research ensuing from such conceptualizations and represents one of the novelties in Skinner's proposal (Staddon & Cerutti, 2003). Reinforcement schedules are arrangements of reinforcement based on certain rules, such as time intervals (e.g., for each response after each period of 30 s since the previous reinforcement) or response requirements (e.g., for each 10th response), which can be varied and combined to form a wide range of complex schedules (Ferster & Skinner, 1957).…”
mentioning
confidence: 99%
“…The other pattern is a constant-responding pattern, in which responding resumes after the postreinforcement pause and occurs with a constant rate until the end of the interval. Considering that the pause may also be influenced by other factors, such as degree of food deprivation, which may decrease after reinforcement, special procedures have been developed to investigate interval timing more accurately (Staddon & Cerutti, 2003). That postreinforcement pauses are also observed in ratio schedules, where reinforcement is dependent on the emission of a given fixed or variable number of responses, suggests that factors other than timing are involved in the production of postreinforcement pauses.…”
mentioning
confidence: 99%